The belt and road initiative: a systematic literature review and future research agenda. Issue 1 (2nd January 2022) - Panibratov, Andrei; Kalinin, Alexey; Zhang, Yugui; Ermolaeva, Liubov; Korovkin, Vladimir; Nefedov, Konstantin; Selivanovskikh, Louisa
ABSTRACT: The Belt and Road Initiative (BRI) has attracted substantial academic attention right after its establishment in 2013. It has produced an array of scientific works analyzing various aspects of this multi-component phenomenon. Our paper is an attempt to systematically classify and further scrutinize the BRI literature within the management and economics field in order to navigate further academic inquiry into the BRI phenomenon. We used the Scopus database and a guided delimitation approach to ensure the quality and relevance of the selected papers. Based on the identified themes we propose promising avenues for future research within the Economics and Management research domain.